Late Pleistocene-Holocene sedimentary records of climate and lake-level changes in Lake Hazar, eastern Anatolia, Turkey - Eris, Kursad Kadir (Pergamon-Elsevier Science Ltd, 2013)
The sedimentary record of Lake Hazar has been documented by detailed seismo- and chronostratigraphic analyses using high-resolution seismic profiles and sediment cores. In this study, two main seismic stratigraphic units can be confidently correlated with sediment cores using lithology and physical properties. As a result of radiocarbon AMS dating, these sedimentary units presumably cover the period from the late Pleistocene to Holocene. The Holocene sequence of the lake infills can be subdivided into five subunits, each subject to distinctive hydrological and sedimentological processes due to fluctuating lake level. The elevations of these deposits including coastal paleo-terraces provide history of the lake level changes. In Lake Hazar, the maximum lowstand lake level occurred during the transition from the Younger Dryas to Holocene, when the -73 m wave-cut terrace was formed as the main shelf-crossing unconformity surface. The beginning of the Holocene was associated with a abrupt lake level rise and resultant deepening. Analysis of the Lake Hazar terraces has the potential to provide complementary data on the chronology of past lake level and lake volume changes, and their link to past climate change. The continued rising lake level during beginning of the Holocene was modulated by stillstands at -63 m and 56 m, as indicated by broad coastal paleo-terraces across the northern shelf. The main shelf-margin sedimentary system for the Holocene period is composed of three distinct buried deltaic-complexes that were presumably sourced from the Kiirkcayi River, the largest input into Lake Hazar. The 3rd millennium crisis at around 3 C-14 ka BP is recorded in the seismic and core data when the cold and dry climatic condition gave rise to a significant lake level drop. (C) 2012 Elsevier Ltd and INQUA. All rights reserved.
Keywords: Strike-Slip Basin; Mediterranean Sea; Van Turkey; Fault; Evolution; Atlantic; Scale